Impact potentiel sur l'environnement - Leeuw, P.N. de (CIPEA, 1992)
As the problems of impact assessement are rather intractable, a fairly simple dual approach is proposed. First the major components of environmental impact of current agricultural production systems in Africa (i.e. impact of cropping, livestock keeping, fuelwood and timber extraction and burning) are summarised. Second, "danger zones" in which current and future environmental impacts will be most severe and on which ILCA has focused its problem solving-research is identified. Positive and negative effects of ILCA's proposed technologies for these stressed areas are briefly examined by reviewing case studies of ILCA's zonal projects.